2020
DOI: 10.1016/j.polymdegradstab.2019.109002
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolytic kinetic model predicting embrittlement in thermoplastic elastomers

Abstract: A hydrolytic kinetic model predicting chains scissions of a polyurethane elastomer (TPU) containing an anti-hydrolysis agent (stabilization via carbodiimide) was developed. This model is based on four components: uncatalysed hydrolysis, acid-catalysed hydrolysis, carboxylic acid dissociation and competitive carbodiimide-based deactivation of acid. Protons were considered as the key catalyst responsible for the hydrolysis. Model parameters were determined by fitting experimental data measured on unstabilized an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…The effect of temperature is shown in Figure 4 for PEBA immersed in seawater and TPU-ether in air. Temperature influence on TPU-ester hydrolysis can be found in Bardin et al 26 In conclusion, this molar mass decline is observed for all polymers in all exposure conditions. However, the kinetics are greatly affected by the TPE chemical structure as well as the nature and temperature of exposure.…”
Section: Macromolecular Changesupporting
confidence: 61%
See 4 more Smart Citations
“…The effect of temperature is shown in Figure 4 for PEBA immersed in seawater and TPU-ether in air. Temperature influence on TPU-ester hydrolysis can be found in Bardin et al 26 In conclusion, this molar mass decline is observed for all polymers in all exposure conditions. However, the kinetics are greatly affected by the TPE chemical structure as well as the nature and temperature of exposure.…”
Section: Macromolecular Changesupporting
confidence: 61%
“…TPU‐ester shows the fastest degradation, TPU‐ether is the most resistant, and PEBA has an intermediate behavior. In a previous study, 26 we clearly identified that the scission phenomenon (causing the molar mass decrease) observed for TPU‐ester was due to hydrolysis. Here we assume that the same phenomenon occurs in PEBA and TPU‐ether.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations